Scoping study on building resilient groundnut and millet value chains in Senegal - Kumar, Shalander; Beye, Assane; Gueye, Fama; Das, Abhishek; Yessoufou, Adjani Nourou-Dine; Faye, Aliou; Worou, Nadine; Whitbread, Anthony M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The cultivation of groundnuts and millet, which has historically been the cornerstone of Senegal's agricultural economy, continues to be an essential component in the nation's efforts to lift its rural population out of poverty. However, increased climatic variability, extreme weather events and market risk has resulted in increased vulnerability of the groundnut and millet value chains impacting the rural livelihoods adversely. As part of the AICCRA project this scoping aims analyses the current situation of the groundnut and millet value chains in terms of performance, access to technologies, climate information delivery and vulnerability and resilience. It also attempts to map the value chain stakeholders and their functions. This report is groundwork to undertake further research to build and assess dynamic value chain model to inform policy makers, stakeholders and development agencies in creating favourable frameworks and design interventions that can promote resilience, farmers’ profitability, efficiency, competitive businesses, sustainable development, poverty alleviation and environmental protection in targeted regions.